Уменьшение продольного изгиба стебля сверла при глубоком сверлении - Пестунов, В. М.; Свяцкий, В. В.; Свяцкая, Л. П.; Pestunov, V.; Sviatskyi, V.; Sviatska, L. („Бял ГРАД - БГ” ООД, 2009)
Рассмотрена схема разгрузки стебля сверла для обработки глубоких отверстий созданием избыточного давления СОТС в зоне резания. Такая комбинированная обработка отверстий решает задачу снижения составляющих технологической нагрузки и позволяет расширить технологические возможности процесса сверления по глубине обработки. The scheme of unloading the drill stem for processing deep drilling by creating an overpressure of lubricant-cooling agent in the cutting zone is considered. Such combined processing of holes solves the problem of reducing the components of the technological load and allows to expand the technological capabilities of the drilling process at the depth of processing.
Reduced longitudinal bend of drill stem with deep drilling
Keywords: глибокое сверление; разгрузка сверла; избыточное давление; СОТС; зона резания; deep drilling; unloading the drill; overpressure; lubricant-cooling agent; cutting area